Syphilis in pregnant women and congenital syphilis from 2012 to 2021 in Switzerland: a multicentre, retrospective study - Chloé Alberto; Noémie Wagner; Yves Fougère; Patrick M. Meyer Sauteur; Gioia Scherler; Karoline Aebbi-Popp; Marc Baumann; Nina Schöbi; Gaud Catho; Stéphane Emonet; Christian Polli; Lisa Kottanattu; et al. (Swiss Medical Weekly, 2024)
BACKGROUND AND AIMS OF THE STUDY: Congenital syphilis is a rare complication of syphilis in pregnant women. Vertical transmission may occur at any time during pregnancy. The incidence of congenital syphilis has been increasing worldwide. Congenital syphilis has been a notifiable disease for many years in Switzerland but reporting does not include maternal features associated with syphilis in pregnancy or infantʼs subsequent development. We described syphilis cases among pregnant women screened over a 10-year period in Switzerland and subsequent cases of congenital syphilis, in order to identify maternal risk profiles and to optimise prevention. Second, we compared the characteristics of pregnant women screened early (1st trimester) vs late in pregnancy (2nd or 3rd trimester). Finally, we assessed the risk factors for premature birth among these women with syphilis.